2015
DOI: 10.1158/0008-5472.can-15-1989
|View full text |Cite
|
Sign up to set email alerts
|

The Inescapable Influence of Noncoding RNAs in Cancer

Abstract: This report summarizes information presented at the 2015 Keystone Symposium on “MicroRNAs and Noncoding RNAs in Cancer”. Nearly two decades after the discovery of the first microRNA (miRNA), the role of noncoding RNAs in developmental processes and the mechanisms behind their dysregulation in cancer has been steadily elucidated. Excitingly, miRNAs have begun making their way into the clinic to combat disease such a hepatitis C, and various forms of cancer. Therefore, at this Keystone meeting novel findings wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…The role of lncRNAs in resistance to endocrine therapy is an area of emerging interest (48, 49). However, our study is, to our knowledge, the first to focus on the impact of a lncRNA on outcomes in a large prospective trial of AI therapy in women with early-stage breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lncRNAs in resistance to endocrine therapy is an area of emerging interest (48, 49). However, our study is, to our knowledge, the first to focus on the impact of a lncRNA on outcomes in a large prospective trial of AI therapy in women with early-stage breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is the fifth most prevalent malignancy and accounts for 85–90% of all primary liver cancer cases ( 29 ). A number of studies have reported that lncRNAs serve an important function in the regulation of gene expression in cancer development ( 30 – 32 ). The dysregulation of lncRNAs has been identified in various types of cancer, including HOTAIR in ovarian and colorectal cancer, GAS5 in breast cancer and MALAT1 in prostate cancer ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Small RNAs or microRNAs (miRNAs) are endogenous, small (~18-24 nt), non-coding RNAs that are key regulators of gene expression. They function post-transcriptionally by binding to complementary sequences of the 3′-untranslated region (3′-UTR) of target mRNAs [21] and play an important role in the regulation of proliferation, differentiation, migration, and apoptosis [22]. The role of miRNA in brain development, neurodevelopmental disorders, and viral infections is well established [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%